Creating Welfare for Micro, Small, and Medium Enterprises During the Covid-19 Pandemic: Role of the State - Debora Debora; Haposan Siallagan; Michelle Lucky Madelene (Law Review, 2022)
The Covid-19 pandemic has weakened the performance of the financial services industry and ruined the Indonesian economy and the welfare of society, including the creative economy sector. Access to finance is often a major problem for Micro, Small, and Medium Enterprises (MSMEs). The role of MSMEs is very much needed in multidimensional, namely economic, social, environmental, and community. However, the role of MSMEs is often constrained in terms of capital accessibility. This study focuses on how the legal protection for MSMEs in the welfare state and how the role of the State in realizing welfare for MSMEs during the Covid-19 Pandemic. This research uses normative juridical research, namely examining material law which contains normative legal principles. This study concludes that first, welfare will be realized if the Government is able to provide legal protection to MSMEs. In order to provide legal protection for MSMEs, this is realized through the existence of Law Number 20 of 2008 concerning MSMEs. Second, the Government has compiled 9 programs to anticipate the impact of Covid-19 on MSMEs. The form of support provided starting from coaching, mentoring, and funding is an effort by the state to prosper the community, especially MSMEs.